PKM Revenue Optimization Strategy UMKM BATIK Pamekasan During the Covid-19 Pandemic using Biogas Stoves, Improvement of Marketing and Managerial Systems - Sandy Vikky Arianto; Syaiful Syaiful; Ria Kasanova; Fredy Yunanto; Mohammad Rudiyanto (COVIT (Community Service of Health), 2022)
Based on the observations of the PKM TEAM, Partners experienced a drastic decline in sales and were predicted to go out of business due to the Covid 19 pandemic. The decline in sales and high production costs were due to PPKM. With a combination of knowledge from Biogas Renewable Energy (Physical Sciences), Quality and Quantity Management (Physical Sciences and Management Sciences), Financial Management (Economics), Marketing Management (Economics and Business Sciences) and even taking care of business licenses (Legal and Administrative Sciences) , and online sales using the Application (Informatics Engineering). This scientific combination method is carried out, in order to maximize the batik production process in UMKM ISHAK Batik, Managerial UMKM ISHAK Batik and batik sales using Offline and Online. This method can increase sales of Batik despite the PPKM implemented by the Indonesian government. The increase in sales is about 25% of the batik production fund. This article is a summary of PKM implementation activities. Keywords: Biogas, Batik, Offline and Online Marketing, Pamekasan, Covid-19